2014
DOI: 10.7554/elife.01958
|View full text |Cite
|
Sign up to set email alerts
|

MUL1 acts in parallel to the PINK1/parkin pathway in regulating mitofusin and compensates for loss of PINK1/parkin

Abstract: Parkinson's disease (PD) genes PINK1 and parkin act in a common pathway that regulates mitochondrial integrity and quality. Identifying new suppressors of the pathway is important for finding new therapeutic strategies. In this study, we show that MUL1 suppresses PINK1 or parkin mutant phenotypes in Drosophila. The suppression is achieved through the ubiquitin-dependent degradation of Mitofusin, which itself causes PINK1/parkin mutant-like toxicity when overexpressed. We further show that removing MUL1 in PINK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
256
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(266 citation statements)
references
References 69 publications
7
256
3
Order By: Relevance
“…By contrast, the mitochondrial E3 ubiquitin ligase MUL1 is transcriptionally upregulated under mitochondrial stress through a mechanism involving FoxO1 and FoxO3 transcription factors (Lokireddy et al, 2012). Elevated levels of MUL1 lead to the ubiquitylation and proteasomal degradation of Mfn2, finally culminating in mitophagy (Lokireddy et al, 2012;Yun et al, 2014). Either relocation of a cytosolic ligase to the mitochondria or transcriptional upregulation of a mitochondrial ligase under stress helps recruit the molecular components required for mitophagy.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the mitochondrial E3 ubiquitin ligase MUL1 is transcriptionally upregulated under mitochondrial stress through a mechanism involving FoxO1 and FoxO3 transcription factors (Lokireddy et al, 2012). Elevated levels of MUL1 lead to the ubiquitylation and proteasomal degradation of Mfn2, finally culminating in mitophagy (Lokireddy et al, 2012;Yun et al, 2014). Either relocation of a cytosolic ligase to the mitochondria or transcriptional upregulation of a mitochondrial ligase under stress helps recruit the molecular components required for mitophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of fission reduces mitophagy, resulting in the accumulation of damaged mitochondria. Depolarization also causes the loss of Mfn1 and Mfn1 on mitochondria and thereby promotes mitochondrial fission, leading to Parkin-and/or Mul1-mediated mitophagy [46,68]. Another study by Lee et al [69] showed that inhibition of Drp1 or overexpression of Mfn1 prevented BNIP3-mediated mitophagy.…”
Section: Mitochondrial Fragmentation In Mitophagymentioning
confidence: 99%
“…Mul1 was shown to induce mitophagy in skeletal muscles [45]. A recent study in Drosophila and mammalian cells revealed that Mul1 acted in parallel to the PINK1/parkin pathway in regulating mitofusin degradation and compensated for the loss of PINK1/parkin, and Mul1 did not affect Parkin-mediated mitophagy [46]. …”
Section: Pink1-parkin Pathway Of Mitophagymentioning
confidence: 99%
“…It is not uncommon for an E3 ubiquitin ligase to be multifunctional and have different substrates. For example, MAPL itself has several known substrate proteins in different physiological processes, including the mitochondrial and peroxisomal fission factor dynaminrelated protein DRP1 (Braschi et al, 2009), E3 ubiquitin ligase TRAF2 in mitochondrial hyperfusion (Zemirli et al, 2014), ULK1 in mitophagy (Li et al, 2015), mitofusin in mitochondrial integrity maintenance (Yun et al, 2014), RIG-I in mitochondrial antiviral response (Jenkins et al, 2013), the Ser/Thr kinase Akt in cell proliferation and viability (Bae et al, 2012), and p53 and p73 when they translocate to mitochondria under cell stress (Jung et al, 2011;Min et al, 2015). When we performed a phylogenetic analysis using SP1, its two homologs from Arabidopsis SPL1 and SPL2, and homologous sequences from other eukaryotic species, MAPL was grouped together with SP1 and SPL1 in the same subclade conserved in plants and animals, whereas SPL2 belonged to a plant-specific subclade, suggesting a strong evolutionary relationship between SP1 and MAPL (Pan et al, 2016).…”
mentioning
confidence: 99%